Psychedelic Therapy's Transdiagnostic Effects: A Research Domain Criteria (RDoC) Perspective - Kelly, John R.; Gillan, Claire M.; Prenderville, Jack; Kelly, Clare; Harkin, Andrew; Clarke, Gerard; O'Keane, Veronica (Frontiers in Psychiatry, 2021)
Accumulating clinical evidence shows that psychedelic therapy, by synergistically combining psychopharmacology and psychological support, offers a promising transdiagnostic treatment strategy for a range of disorders with restricted and maladaptive habitual patterns of cognition and behaviour, notably, depression (MDD), treatment resistant depression (TRD) and addiction disorders, but perhaps also anxiety disorders, obsessive-compulsive disorder (OCD), Post-Traumatic Stress Disorder (PTSD) and eating disorders. Despite the emergent transdiagnostic evidence, the specific clinical dimensions that psychedelics are efficacious for, and associated underlying neurobiological pathways, remain to be well characterised. To this end, this review focuses on pre-clinical and clinical evidence of the acute and sustained therapeutic potential of psychedelic therapy in the context of a transdiagnostic dimensional systems framework. Focusing on the Research Domain Criteria (RDoC) as a template, we will describe the multimodal mechanisms underlying the transdiagnostic therapeutic effects of psychedelic therapy, traversing molecular, cellular and network levels. These levels will be mapped to the RDoC constructs of negative and positive valence systems, arousal regulation, social processing, cognitive and sensorimotor systems. In summarising this literature and framing it transdiagnostically, we hope we can assist the field in moving towards a mechanistic understanding of how psychedelics work for patients and eventually towards a precise-personalized psychedelic therapy paradigm.